Association of Poor Sleep Burden in Middle Age and Older Adults With Risk for Delirium During Hospitalization. Issue 3 (24th September 2021) - Ulsa, Ma Cherrysse; Xi, Zheng; Li, Peng; Gaba, Arlen; Wong, Patricia M; Saxena, Richa; Scheer, Frank A J L; Rutter, Martin; Akeju, Oluwaseun; Hu, Kun; Gao, Lei
Abstract: Background: Delirium is a distressing neurocognitive disorder recently linked to sleep disturbances. However, the longitudinal relationship between sleep and delirium remains unclear. This study assessed the associations of poor sleep burden, and its trajectory, with delirium risk during hospitalization. Methods: About 321 818 participants from the UK Biobank (mean age 58 ± 8 years [ SD ]; range 37–74 years) reported (2006–2010) sleep traits (sleep duration, excessive daytime sleepiness, insomnia-type complaints, napping, and chronotype—a closely related circadian measure for sleep timing), aggregated into a sleep burden score (0–9). New-onset delirium ( n = 4 775) was obtained from hospitalization records during a 12-year median follow-up. About 42 291 (mean age 64 ± 8 years; range 44–83 years) had repeat sleep assessment on average 8 years after their first. Results: In the baseline cohort, Cox proportional hazards models showed that moderate (aggregate scores = 4–5) and severe (scores = 6–9) poor sleep burden groups were 18% (hazard ratio = 1.18 [95% confidence interval: 1.08–1.28], p < .001) and 57% (1.57 [1.38–1.80], p < .001), more likely to develop delirium, respectively. The latter risk magnitude is equivalent to 2 additional cardiovascular risks. These findings appeared robust when restricted to postoperative delirium and after exclusion of underlying dementia. Higher sleep burden was also associated with delirium in the follow-up cohort. Worsening sleep burden (score increase ≥2 vs no change) further increased the risk for delirium (1.79 [1.23–2.62], p = .002) independent of their baseline sleep score and time lag. The risk was highest in those younger than 65 years at baseline ( p for interaction <.001). Conclusion: Poor sleep burden and worsening trajectory were associated with increased risk for delirium; promotion of sleep health may be important for those at higher risk.